Mutual Fund Investing: One of the Main Ways of Saving for Retirement in Russia - Tatiana Sedash (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2006)
One of the most acute problems in the world today is provision of a respectable living for the elderly. Today the process of aging population (as a result of a declined birth rate and increased life expectancy) has touched all countries of the world - developed countries as well as countries like Russia. Consequently, reforming traditional pension systems to deal with the changing situation has become an important issue around the world. These reforms typically center on the implementation of some form of funding of future pension benefits. This also holds for Russia, where in 1995 pension reform legislation introduced the so-called 'accumulation pension'. In this context, this article will deal with the issues concerning the establishment of mutual funds, legal aspects of their operating and their investing opportunities. There will be carried out a comparative analysis of mutual funds with the other forms of public investments, namely: Common Funds of Bank Management, Voucher Investment Funds and Joint-stock Investment Funds.
Keywords: G23; G21; G28; 330